Investigation of maraging steel M789 parts fabricated by direct energy deposition - Hon, Cheng Hui (Nanyang Technological University, 2022)
M789 is a newly developed additively manufactured maraging steel designed to have high strength and high corrosion resistance. However, there is a research gap in the characterization of microstructure and mechanical properties of M789 steel parts printed by directed energy deposition (DED). In this report, microstructural analysis and mechanical tests were conducted. Additionally, the effects of heat treatment on M789 were thoroughly investigated. Microstructural analysis was done using an optical microscope and scanning electron microscope equipped with an electron backscatter diffraction (EBSD) detector on various as-printed and heat-treated M789 samples. EBSD analysis reveals that the samples mainly consist of a martensitic structure with the presence of austenite in the as-printed and some heat-treated samples. Additionally, mechanical tests such as tensile tests, Vickers hardness tests, and nanoindentation were done to characterize the mechanical properties of M789 heat-treated at different temperatures. The results indicate that solution-ageing at 500 ℃ for two hours is the optimal heat treatment strategy to yield the highest ultimate tensile strength for M789 parts printed by DED.